Compact waveguide‐based corporate‐fed array antenna with wideband and high‐gain performance in E‐band. Issue 6 (12th March 2022) - Yun, Yu; Liu, Ying; Liu, Neng‐Wu; Wu, Zhe; Zheng, Yuling; Lennerstad, Håkan
Abstract: A compact, high‐gain 32 × 32‐horn array antenna with wideband and low side‐lobes for millimeter‐wave applications in the E‐band (71–86 GHz) is presented. The antenna is composed of four metallic layer structures under the waveguide‐feeding. The top layer contains the horn elements and the bottom layer is a corporate‐fed network. From top to bottom, the 2 × 2 cavity‐backed sub‐arrays and the T‐shaped waveguide junctions are loaded in the middle layers. The RF signal from the planar 1–256 ways divider is fed to the horn elements. Due to the uniform excitation, the antenna acquires the high‐gain pencil beam. To verify this design concept, the antenna has been fabricated, measured, and evaluated. Experimental results show that the antenna array has achieved an improved bandwidth (|S11| < −10 dB) in the range of 71–86 GHz (19.1%). More importantly, the peak gain of the proposed antenna keeps a high value of around 38 dBi with the ETSI (European Telecommunications Standards Institute) class II radiation pattern envelope (RPE).